Agricultural practices and technologies to enhance food security, resilience and productivity in a sustainable manner: Messages to the SBSTA 44 agriculture workshops - Dinesh, Dhanush (2016)
This paper synthesizes knowledge within CGIAR and its partners on agricultural practices and technologies to enhance food security, resilience and productivity in a sustainable manner. A number of agricultural practices and technologies which contribute to these objectives were identified and assessed to generate four key lessons. Firstly, agricultural practices and technologies do not necessarily have universal applicability, they will have to be selected, tailored and applied as appropriate for the context, including agro-ecological zones, farming systems as well as cultural and socio-economic context. Secondly, strong mechanisms for capacity enhancement and technology transfer are prerequisites for success of interventions. Thirdly, suitable sources of funding are required to support implementation and scaling up efforts. Lastly, many agricultural practices and technologies have the potential to achieve co-benefits for environmental health and climate change mitigation. In contexts where mitigation is feasible, managing for multiple outcomes can help countries and smallholder farmers adopt low carbon development pathways. This Working Paper is related to this Info Note: http://hdl.handle.net/10568/71051